2020
DOI: 10.1152/japplphysiol.00247.2020
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with an exaggerated blood pressure response to ischemic rhythmic handgrip exercise in nondiabetic older adults

Abstract: The diastolic blood pressure response to rhythmic dynamic handgrip exercise under ischemic conditions was demonstrated to be correlated with insulin resistance-related factors in nondiabetic older adults. This finding provides important insight to the prescription of exercise in this particular patient population as the blood pressure response to exercise, especially under ischemic conditions, could be exaggerated to nonsafe levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Although it is possible that the lower-intensity rhythmic exercise did not produce sufficient metabolic stimuli to unmask a difference in metaboreflex-induced BP responses between groups, notably T2D patients in this study exhibited exaggerated vasoconstriction during PEI. Interestingly, a recent study showed enhanced BP responses to ischemic rhythmic handgrip exercise (30% MVC) in nondiabetic individuals with greater insulin resistance than those with lower insulin resistance (Hotta et al, 2020). Overall, the existing literature supports that both components of the exercise pressor reflex (i.e., mechanoand metabo-reflex) may be enhanced in T2D (Figure 2).…”
Section: Neurovascular Dysregulation During Exercise In Type 2 Diabetesmentioning
confidence: 85%
See 1 more Smart Citation
“…Although it is possible that the lower-intensity rhythmic exercise did not produce sufficient metabolic stimuli to unmask a difference in metaboreflex-induced BP responses between groups, notably T2D patients in this study exhibited exaggerated vasoconstriction during PEI. Interestingly, a recent study showed enhanced BP responses to ischemic rhythmic handgrip exercise (30% MVC) in nondiabetic individuals with greater insulin resistance than those with lower insulin resistance (Hotta et al, 2020). Overall, the existing literature supports that both components of the exercise pressor reflex (i.e., mechanoand metabo-reflex) may be enhanced in T2D (Figure 2).…”
Section: Neurovascular Dysregulation During Exercise In Type 2 Diabetesmentioning
confidence: 85%
“…Studies are also needed to further understand the contribution of factors such as insulin resistance, obesity, and physical inactivity. Notably, two studies indicate that insulin resistance may be a stronger predictor of an augmented metaboreflex than obesity in nondiabetic individuals (Milia et al, 2015;Hotta et al, 2020). However, others have demonstrated that obesity may drive negative effects on neural cardiovascular control mechanisms in T2D patients (Holwerda et al, 2016b).…”
Section: Considerations and Future Directionsmentioning
confidence: 99%
“…PWM and RHG exercise were performed during the 2nd (PEMI + PWM) and the 3rd minute of PEMI (PEMI + RHG), respectively, after a 1 min rest period (PEMI + Rest) which we defined as the second baseline. This protocol was based on a previous study (Hotta et al, 2020 ). Exp.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of the IHG exercise was set at 30% of the individual's maximum voluntary contraction (MVC) force (Cui et al, 2008 ; Hotta et al, 2020 ; Park et al, 2008 ; Williamson et al, 2002 ), which was determined previously. Participants maintained their gripping force using a visual feedback system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation